2006
DOI: 10.1002/hep.21103
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and differences in outcomes of cirrhosis due to nonalcoholic steatohepatitis and hepatitis C

Abstract: The objective of this study was to prospectively define outcomes of cirrhosis due to nonalcoholic steatohepatitis (NASH) and compare them with those associated with hepatitis C virus (HCV) infection. We compared 152 patients with cirrhosis due to NASH with 150 matched patients with cirrhosis due to HCV. Over 10 years, 29/152 patients with cirrhosis due to NASH died compared with 44/150 patients with HCV (P < .04). This was mainly due to the lower mortality rate in patients with Child class A cirrhosis due to N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
355
2
10

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 468 publications
(390 citation statements)
references
References 41 publications
(48 reference statements)
18
355
2
10
Order By: Relevance
“…[48][49][50][51][52][53] Several studies investigated the natural history of NASH cirrhosis in comparison to patients with hepatitis C cirrhosis. [54][55][56][57] One large prospective US-based study 55 observed a lower rate of decompensation and mortality in patients with NASH cirrhosis as compared to patients with hepatitis C cirrhosis. However, a more recent international study 56 of 247 NAFLD patients with advanced fibrosis and cirrhosis followed over a mean duration of 85.6 6 54.5 months showed an overall 10-year survival of 81.5% that was not different from matched patients with hepatitis C cirrhosis.…”
Section: Natural Historymentioning
confidence: 99%
See 1 more Smart Citation
“…[48][49][50][51][52][53] Several studies investigated the natural history of NASH cirrhosis in comparison to patients with hepatitis C cirrhosis. [54][55][56][57] One large prospective US-based study 55 observed a lower rate of decompensation and mortality in patients with NASH cirrhosis as compared to patients with hepatitis C cirrhosis. However, a more recent international study 56 of 247 NAFLD patients with advanced fibrosis and cirrhosis followed over a mean duration of 85.6 6 54.5 months showed an overall 10-year survival of 81.5% that was not different from matched patients with hepatitis C cirrhosis.…”
Section: Natural Historymentioning
confidence: 99%
“…Importantly, both studies have shown that patients with NASH cirrhosis are at significantly lower risk for HCC than patients with hepatitis C cirrhosis. 55,56 Alcohol Consumption & Definition of NAFLD By definition, NAFLD indicates the lack of any evidence of ongoing or recent consumption of significant quantities of alcohol. However, the precise definition of significant alcohol consumption in patients with suspected NAFLD is uncertain.…”
Section: Natural Historymentioning
confidence: 99%
“…4 The clinical implications of this alarming prevalence of NAFLD are derived from the fact that NAFLD may progress to cirrhosis, liver failure, and HCC. [5][6][7][8] Within the spectrum of NAFLD, simple bland steatosis often remains stable for a number of years and will probably never progress in many patients. 9,10 A subset of patients, however, particularly those with more advanced fibrosis, are at a higher risk for progressing to decompensated cirrhosis, portal hypertension, HCC, or death if liver transplantation is not accomplished.…”
mentioning
confidence: 99%
“…9,10 A subset of patients, however, particularly those with more advanced fibrosis, are at a higher risk for progressing to decompensated cirrhosis, portal hypertension, HCC, or death if liver transplantation is not accomplished. [5][6][7][8][11][12][13][14] In contrast to patients with bland steatosis, patients with increased liver fibrosis require close follow-up with surveillance for the development of esophageal varices and HCC and enrollment into treatment trials. Thus, identifying the presence and severity of liver fibrosis in patients with NAFLD is of major importance in guiding the subsequent management of patients with this liver condition.…”
mentioning
confidence: 99%
“…However, in a systematic review of paired biopsy studies only the presence of inflammation of any grade and increased age were independent risk factors for fibrosis progression. In another study, patients with cirrhosis due to NAFLD were compared to a group of patients with cirrhosis due to the hepatitis C virus (36) . Patients from both groups were most likely to die from complications of sepsis.…”
Section: Does Hepatic Steatosis Increase Morbidity and Mortality?mentioning
confidence: 99%